Thin-channel AlGaN/GaN/AlN double heterostructure HEMTs on AlN substrates via hot-wall MOCVD - Kim, Minho; Papamichail, Alexis; Tran, Dat Q.; Paskov, Plamen P.; Darakchieva, Vanya (Applied Physics Letters, 2025)
III-Nitride high-electron mobility transistors (HEMTs) grown on AlN substrates offer significant advantages for high-power, high-frequency applications due to AlN high thermal conductivity and ultra-wide bandgap. However, achieving high-quality thin GaN channel layers on AlN is challenging because of lattice mismatch, which leads to columnar growth. In this work, we present the development of a two-step growth process with controlled carbon incorporation that enables fully coalesced 150 and 50-nm-thick GaN channel layers on AlN substrates by hot-wall metalorganic chemical vapor deposition. We demonstrate HEMTs with state-of-the-art two-dimensional electron gas mobility values of 1805 and 1100 cm2/V s for the 150-nm-thick and the 50-nm-tick channels, respectively. Thermal transport analysis, incorporating experimentally measured thermal conductivities of the individual HEMT components and electro-thermal simulations via Technology Computer-Aided Design, reveals a 19% reduction in surface temperature for devices on AlN substrates compared to similar HEMTs on SiC. This result highlights the thermal management benefits of homoepitaxy on AlN